Surveillance of antibiotic resistance in the northern zone of Senegal: Molecular characterization of beta-lactam resistance genes in Enterobacteriaceae (extended spectrum beta-lactamase, plasmid cephalosporinases, carbapenemases). - Kane, Amadou; LO, S.; Diakhaby, M. E. B.; Dièye, Y.; Diallo, O. F.; Faye, C. I.; Diao, S.; Ndiaye, M.; Guèye, C.; Doupa, D.; et al. (British Journal of Healthcare and Medical Research, 2023)
Introduction: With the increase in bacterial resistance to antibiotics, policies are being implemented on a national scale. These resistances are multiple, especially in enterobacteria, and represent a real public health problem due to the difficulty of their treatment. The objective of this work was to identify ESBL, cephalosporinase and carbapenemase producing enterobacteria in laboratories in the northern part of Senegal and to compare the mechanisms involved. Materials and methods: This is a retrospective study conducted at the Saint-Louis Regional Hospital and the Microbiology Unit of the Pasteur Institute of Dakar. Bacterial strains were collected between January and June 2021 in eight bacteriology laboratories in the regions of Saint-Louis, Louga and Matam. Bacterial identification was done by studying morphological, cultural and biochemical characteristics using an API® 20 E gallery and the MALDI-TOFF technique. The antibiogram was performed by the disc diffusion method according to the CA-SFM version 2021 procedure including the search for specific resistances (ESBL). The ESBL genes (CTX, TEM, OXA, and SHV) were identified by polymerase chain reaction (PCR) with specific primers and then analyzed by gel electrophoresis. Results: Forty-five strains of Enterobacteriaceae were ESBL producers and each had at least one beta-lactam resistance gene. The CTX-M gene was found in all strains, followed by the OXA (64.44%), TEM (53.33%) and SHV (20%) genes. A simultaneous presence of these 4 genes was noted in 6 isolates (13.33%). Apart from resistance to ertapenem, all strains were sensitive to imipenem. For quinolones, almost all strains (93%) were resistant. Conclusion: These results show the need to reinforce the surveillance of ESBL-producing Enterobacteriaceae in the Senegal area. These important data should help to orientate strategies for the reduction of MRBs and their dissemination in the community.